The Effect of Product Quality and Service Quality on Repurchase Intention with Customer Satisfaction as an Intervening Variable (A Case Study at Gudang AKI Denpasar) - Nailun Ni'mah; Gusti Ngurah Joko Adinegara; Yeyen Komalasari; I Wayan Ruspendi Junaedi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study examines the effects of product quality (X1) and service quality (X2) on repurchase intention (Y), with customer satisfaction (Z) as a mediating variable among customers of Gudang Aki Denpasar. The research was conducted during March–June 2024 using a quantitative approach and primary data collected through questionnaires. The sample size was determined using Slovin’s formula, resulting in 99 respondents. Data were analyzed using SEM-PLS with SmartPLS 4.1 to test both direct and indirect relationships. The structural results indicate that product quality has a positive and significant effect on repurchase intention and a positive and significant effect on customer satisfaction. Service quality also shows a positive and significant effect on repurchase intention and on customer satisfaction. Moreover, customer satisfaction positively and significantly influences repurchase intention. Mediation testing confirms that customer satisfaction partially mediates the effect of product quality on repurchase intention and the effect of service quality on repurchase intention. The model explains the variance of repurchase intention and customer satisfaction, indicating a moderate explanatory power. In conclusion, product quality and service quality have a positive and significant effect on repurchase intention, both directly and through customer satisfaction; customer satisfaction is also proven to partially mediate the effects of product quality and service quality on repurchase intention, indicating that consistent improvements in product and service performance will strengthen satisfaction and encourage repeat purchases at Gudang Aki Denpasar.